Influence of Obesity Diagnosis With Organ Dysfunction, Mortality, and Resource Use Among Children Hospitalized With Infection in the United States. (June 2017) - Maley, Nidhi; Gebremariam, Achamyeleh; Odetola, Folafoluwa; Singer, Kanakadurga
Background: Sepsis induces inflammation in response to infection and is a major cause of mortality and hospitalization in children. Obesity induces chronic inflammation leading to many clinical manifestations. Our understanding of the impact of obesity on diseases, such as infection and sepsis, is limited. The objective of this study was to evaluate the association of obesity with organ dysfunction, mortality, duration, and charges during among US children hospitalized with infection. Methods: Retrospective study of hospitalizations in children with infection aged 0 to 20 years, using the 2009 Kids' Inpatient Database. Results: Of 3.4 million hospitalizations, 357 701 were for infection, 5685 of which were reported as obese children. Obese patients had higher rates of organ dysfunction (7.35% vs 5.5%, P < .01), longer hospital stays (4.1 vs 3.5 days, P < .001), and accrued higher charges (US$29 019 vs US$21 200, P < .001). In multivariable analysis, mortality did not differ by obesity status (odds ratio: 0.56, 95% confidence interval: 0.23-1.34), however severity of illness modified the association between obesity status and the other outcomes. Conclusions: While there was no difference in in-hospital mortality by obesity diagnosis, variation in organ dysfunction, hospital stay, and hospital charges according to obesity status was mediated by illness severity. Findings from this study have significant implications for targeted approaches to mitigate the burden of obesity on infection and sepsis.